Survival difference between surgery versus non-surgery for the treatment of hepatocellular carcinoma patients at Liver Centre, Malaysia - Azmawati MN,; Azmi MT,; Krishnan R, (Department of Surgery, UKM Medical Centre, 2011)
Hepatic resection, the only treatment that offers long term survival for patients with Hepatocellular carcinoma (HCC), have shown significant improvement in results over the past decades. The aim of the study was to compare the survival between patients receiving and not receiving surgery. A retrospective co¬hort study measured the survival of newly diagnosed cases of HCC patients who underwent treatment in Selayang Hospital from 1 January 2003 till 31 December 2006. Survival time was measured from the date of diagnosis until the subjects died or until the end of study period (31 December 2007). Overall survival was significantly longer in surgery group in comparison with non-surgery group with a median survival of 43 and 20 months, respectively (p<0.001). The following factors were noted to have improved survival duration with surgical resection; Child Pugh Class B patients, tumor size less or more than 4cm and number of nodules less than 3. Sub¬group analysis showed improved survival duration with surgical resection among patients with Child Pugh Class B with tumor size less than 4cm or with nodule less than 3 and patients who had less than 3 nodules, even with tumor size of less or more than 4cm. Multivariate Cox Re¬gression showed surgical intervention significantly improved survival time for overall patients (Adjusted HR: 1.5) while non-surgery improved survival in patients with tumor size less than 4cm (Adjusted HR: 0.4). Surgical resection significantly improved the survival duration in over¬all patients while non-surgical procedure improved survival if the tumor size was less than 4cm.